Effects of guanidinoacetic acid and methionine on metabolism and performance in cattle - Ardalan, Mehrnaz (Kansas State University, 2021)
Efficient utilization of feed protein by cattle, because of its impact on economics and the environment, is a major concern for animal nutritionists and producers. Ruminants play an important role in food production (milk and meat) and are major sources of protein for human livelihoods. Two experiments were conducted to assess the value of guanidinoacetic acid (GAA) with or without methionine (Met) on nitrogen retention, methionine flux, and methylation reactions in cattle. As well, a study was conducted to investigate the effectiveness of 2 ruminally protected methionine sources for lactating dairy cows. Another study evaluated effects of abomasal infusions of casein on dairy cattle production. The first experiment examined the effect of abomasal infusions of GAA (0, 10, 20, 30, or 40 g/d GAA) combined with either 0 or 12 g/d of methionine on creatine synthesis and plasma homocysteine concentrations in 6 ruminally cannulated Holstein heifers (520 kg initial body weight). This study demonstrated that plasma creatine was increased by GAA supplementation. Plasma homocysteine was not affected by GAA supplementation when heifers received 12 g/d methionine, but it was increased when 30 or 40 g/d of GAA was supplemented without methionine (GAA-linear x Met, P = 0.003). This experiment demonstrated that post-ruminal GAA supplementation increased creatine supply to cattle and spares arginine utilization. In the second study, effects of GAA supplementation on nitrogen retention and methionine flux were evaluated in 7 ruminally cannulated Holstein steers (161 kg initial body weight) limit-fed a soybean hull-based diet. Treatments were provided abomasally and included 0 or 6 g/d of L- methionine and 0, 7.5, and 15 g/d of GAA. Steers received continuous abomasal infusions of an essential amino acid mixture devoid of methionine to ensure that no amino acid besides methionine limited animal performance, and energy was supplied by ruminal infusion of volatile fatty acids and abomasal infusion of glucose. Whole body methionine flux was measured using continuous jugular infusions of 1-¹³C-L- methionine and methyl-²H₃-L- methionine. Nitrogen retention was elevated by methionine supplementation (P < 0.01). Supplementation with GAA tended to increase N retention when it was supplemented along with methionine, but not when it was supplemented without methionine. Supplementation of GAA increased plasma creatine concentrations GAA and creatine (P < 0.001). Loss of methionine through transsulfuration was increased by methionine supplementation, whereas synthesis of methionine from remethyation was decreased by methionine supplementation. No differences in transmethylation, transsulfuration, or remethylation reactions were observed in response to GAA supplementation. These results showed that administration of GAA, when methyl groups are not limiting, has the potential to improve lean tissue deposition and cattle growth. In the third study, 21 Holstein dairy cows were utilized to study lactational responses of dairy cows to methionine provided from 2 ruminally protected sources of methionine activity. Treatments included: 1) control, 2 and 3) 7.5 and 15 g/d of a ruminally protected product of 2-hydoxy-4-methylthio-butyric acid (NTP-1401; Novus International, Inc., St. Charles, MO), and 4 and 5) 7.5 and 15 g/d of a ruminally protected DL-methionine product (Smartamine M; Adisseo, Alpharetta, GA). Milk protein percentage and milk protein yield increased linearly with supplementation, without differences between methionine sources or interactions between source and level. Plasma methionine concentrations were increased linearly by methionine supplementation, with the increase being greater for Smartamine M than for NTP-1401. Plasma D-methionine was increased only by Smartamine M. Plasma 2-hydoxy-4-methylthio-butyric acid was increased only by NTP-1401. These data demonstrated that supplementation with these methionine sources can improve milk protein percentage and yield, and the 2 methionine sources did not differ in their effect on lactation performance or milk composition. The final study was conducted to evaluate the effect of post-ruminal supplementation of casein on milk yield and composition and whole body protein deposition in dairy cattle. Two ruminally cannulated Holstein dairy cows (599 kg initial body weight) were used. Treatments included daily abomasal infusion of 0 or 400 g/d casein. Cows received 320 g/d glucose through continuous abomasal infusion to prevent energy from being limiting. This study demonstrated that abomasal casein infusion had no effect on milk yield and composition with the exception of milk protein percentage and milk urea nitrogen, which were increased (P < 0.01) when casein was supplemented. Nitrogen retention (P = 0.03) and urinary N excretion (P < 0.0001) were increased and fecal N excretion (P < 0.0001) was decreased by post-ruminal casein infusion. These results suggest that casein has potentially positive effect on stimulating protein deposition and can be used as an effective way to alter nitrogen utilization in lactating dairy cattle.
Keywords: Guanidinoacetic acid; Methionine